Essential commodities prices, availability, and market actors’ perceptions: July 2025 - Siddig, Khalid; Rakhy, Tarig Alhaj; Mohamed, Shima; Abushama, Hala; Nigus, Halefom Yigzaw (International Food Policy Research Institute, 2025)
This report analyzes market dynamics in Sudan between February and July 2025, focusing on prices, availability, quality, fuel, exchange rates, and traders’ perceptions of supply, demand, profits, and market conditions.